Inflammatory Biomarkers in Peripheral Artery Disease: Diagnosis, Prognosis, and Therapeutic Challenges - Ozaki, Yuichi; Imanishi, Toshio; Akasaka, Takashi (Current Medicinal Chemistry, 2015)
Peripheral artery disease (PAD) is an inflammatory disease caused by atherosclerosis. It has been demonstrated that PAD is related to chronic inflammation. While conventional risk factors lead to the pathogenesis and progression of PAD, the role of novel inflammatory biomarkers in relation to PAD is being increasingly recognized. The novel biomarkers for PAD may allow for earlier screening and detection, suppression of disease progression, and development of new therapeutic approaches. In this review, inflammatory biomarkers that should be contributory to diagnosis, prognosis, and avenues for therapeutic challenges in PAD are summarized.
Keywords: Biomarker